Framing of Online Media News about Riots in Papua (Studies on www.detik.com and www.reuters.com in 2019) - Widyaningsih, Seftiana Noorfi; Lestari, Rani Dwi (Jurnal Pekommas, 2020)
This study discusses the framing conducted by detik.com and reuters.com on the issue of the 2019 Papua riots. It is motivated by the tendency of the different news angles from each of these both media. It uses a qualitative method using Robert Entman's media framing theory which divides framing into two large dimensions: the selection of issues and the highlighting of certain aspects of the issue. Studies on two online medias: detik.com and reuters.com are intended to provide a comparison of the ideology between the domestic and foreign media in framing the issues of riots that are in direct dealing with the government. The analysis shows that detik.com conducted an issue selection by describing the riots in Papua as a security issue. This media highlighted aspects of the Indonesian government's role in overcoming the riots. On the other hand, reuters.com described it as a social issue by highlighting aspects of discrimination and violence by the Indonesian government in overcoming the riots.